Kontekstualisasi Nilai Pendidikan Karakter dalam Sirah Nabawiyah: Studi Hermeneutika Pada Pemikiran dan Metode Paul Ricoeur - Fifi Khoirul Fitriyah; Muhammad Sukron Djazilan (Universitas Nahdlatul Ulama Surabaya, 2020)
The purpose of this article is to contextualize the various inspirational stories of the Prophet Muhammad summarized in the Sirah Nabawiyah. The exploration of inspired stories will place more emphasis on the period before prophetic revelation, so as to minimize the reasons for mankind's inability to make Muhammad a role model and an inspirational figure. The contextualization of thought in sirah nabawiyah was carried out using the hermeneutic approach as a method in the tradition of Paul Ricoeur's thought. Hermeneutics in the Paul Ricoeur tradition tries to go beyond modern interpretation which seeks to find an understanding of the meaning between the interpreter and the writer. Therefore, it is possible to produce new meanings of sirah nabawiyah accompanied by a subjective reflection process that is linked to the contextual background. This article generates contextualization and new meanings of the inspirational story of the prophet Muhammad in Sirah Nabawiyah to become eighteen values ​​of character education based on national culture. These character values ​​will be embedded in every level of Indonesian national education.